Self-cleaning active resistance reducing agent and preparation method thereof

By developing a self-cleaning active resistance reducing agent containing a composite copolymer powder and a pro-desorption agent, the problems of thickener adsorption damage and solid residue damage in hydraulic fracturing are solved, and the effects of low adsorption, low residue and high recovery are achieved.

CN119775990AActive Publication Date: 2025-04-08CHENGDU LEARN PRACTICES TECH CO LTD +1

Patent Information

Application Number
CN202510280167.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-11
Publication Date
2025-04-08
Estimated Expiration
2045-03-11

AI Technical Summary

Technical Problem

The existing thickeners have adsorption damage and solid residue damage during hydraulic fracturing, resulting in blockage of reservoir pores and channels, affecting oil and gas flow and recovery efficiency.

Method used

A self-cleaning active resistance reducing agent is developed, including composite copolymer powders, pro-desorption agents, suspension main agents and suspension activators, to reduce the static adsorption of the polymer and the formation of residues by improving the polymer structure and adding components such as urea and bacterial nanocellulose.

Benefits of technology

This resistance reducing agent not only has the functions of reducing resistance and thickening, but can be effectively transported under low adsorption and low residue conditions, has the ability to promote methane desorption and formation cleaning, and improves oil and gas recovery and stable production capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

The invention discloses a self-cleaning active resistance reducing agent and a preparation method thereof, and belongs to the technical field of oilfield chemistry. The resistance reducing agent is prepared from the following components in mass concentration: 30-50% of a composite copolymer, 1-15% of a desorption promoting agent, 0.02-0.4% of a suspension main agent, 0.15-0.6% of a suspension activating agent and the balance of a solvent, the preparation method comprises the following steps: firstly, dissolving polyvinyl alcohol and carboxymethyl hydroxypropyl guanidine gum in water to form an aqueous solution, and adding acrylamide, sodium acrylate, a rigid monomer containing a benzene ring, a reinforcing agent and urea into the aqueous solution to obtain a composite reaction solution; adding an initiator to carry out polymerization reaction to obtain polymer colloid; and cutting, crushing and drying the polymer colloid to obtain composite copolymer powder. The resistance reducing agent disclosed by the invention has a thickening effect, strengthens the characteristics of low adsorption and low residue of a polymer on the basis of having variable viscosity and strong sand-carrying capacity, also has the effects of promoting the dissociation of adsorbed gas into free gas and dredging and cleaning a stratum, and effectively improves the oil and gas recovery ratio and the stable production capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of oilfield chemistry, in particular to a self-cleaning active drag reducing agent and a preparation method thereof. Background Art

[0002] Hydraulic fracturing is the core technology for increasing reserves and production of unconventional oil and gas. Slippery water fracturing fluid with water-soluble thickener as the core is the key material of hydraulic fracturing technology. Variable viscosity emulsion polyacrylamide thickener that matches the volume transformation concept is the main application. However, due to the influence of polymerization technology and suspension technology, there are still a series of problems. (1) Adsorption damage: In order to obtain good resistance reduction and sand carrying performance, ultra-high molecular weight polyacrylamide (PAM) is used. Due to hydrogen bonding and other effects, the polymer is very easy to adsorb to the reservoir. This adsorption phenomenon will cause the pores and channels of the reservoir to be blocked, thereby affecting the flow of oil and gas, and ultimately leading to a decrease in recovery efficiency. (2) Solid residue damage: Solid residue brought by foreign fluids can easily block pore throats, thereby reducing reservoir permeability. The ideal fracturing fluid system should be able to effectively transport fracturing proppants while producing less solid residue and maintaining a high reservoir permeability. However, the existing powder emulsion suspension technology uses a large amount of mineral suspending agents, which brings insoluble residues; inverse emulsion products have oil-water emulsification and form composite residues with polymers.

[0003] The thickeners reported in the related literature in the prior art only partially solve the problems of salt resistance, sand carrying and adsorption of shale reservoirs under low concentration conditions in the slick water stage, or unilaterally optimize the polymer molecular structure. It has not yet been possible to develop a functional self-cleaning fracturing fluid resistance reducer that has low adsorption and low residue for high concentration solutions of different reservoirs and has the ability to promote methane desorption and clean and dredge the formation. Summary of the invention

[0004] In view of the functional defects of existing thickeners such as adsorption damage and solid residue damage, the present invention provides a self-cleaning active drag reducing agent. The drag reducing agent has not only drag reducing function but also thickening function, and can be used as a thickener.

[0005] The self-cleaning active drag reducing agent provided by the present invention comprises the following components in percentage by mass: Composite copolymer powder 30-50%, desorption promoter 1-15%, suspension main agent 0.02-0.4%, suspension activator 0.15-0.6%, and the rest are water-soluble solvents, totaling 100%.

[0006] The preparation method of the composite copolymer is as follows: (1) Polyvinyl alcohol and carboxymethyl hydroxypropyl guar gum are dissolved in water to form an initial composite low molecular weight polymer aqueous solution, and then acrylamide, sodium acrylate, a benzene ring-containing rigid monomer, a reinforcing agent and urea are added to the aqueous solution to obtain a composite reaction solution.

[0007] The benzene ring-containing rigid monomer is selected from any one of the following six molecular structural formulas:

[0008]

[0009] Wherein, the R3 group is -COONa or -SO3Na.

[0010] The molar ratio of acrylamide, sodium acrylate and benzene ring-containing rigid monomer is 1: (0.05-0.4): (0.01-0.1). In the composite reaction solution, the total mass fraction of acrylamide, sodium acrylate and benzene ring-containing rigid monomer is 15-40%.

[0011] In the composite reaction solution, the mass fraction of urea is 1-20%; urea has the functions of desorbing polyacrylamide adsorption and promoting dissolution.

[0012] The enhancer is N,N-methylenebisacrylamide. In the composite reaction solution, the enhancer concentration is 20-1000 mg / L, more preferably 100-500 mg / L, and most preferably 100-200 mg / L.

[0013] The initiator is a redox initiation system composed of ammonium cerium nitrate and sodium bisulfite, with a mass ratio of 1: 1. The concentration of ammonium cerium nitrate in the composite reaction solution is 30-200 mg / L, preferably 60-150 mg / L, and most preferably 80-120 mg / L.

[0014] The molecular weight of the polyvinyl alcohol is 10,000-150,000, preferably 20,000-120,000, more preferably 30,000-100,000, and optimally 50,000-80,000. The alcoholysis degree is 80-85%. The mass fraction of the polyvinyl alcohol in the polymerization system is 0.5-6%, preferably 1-5%, more preferably 1-4%, and optimally 1.5-3%.

[0015] The molecular weight of the carboxymethyl hydroxypropyl guar gum is 50×10 4 -200×10 4 , the optimal value is 100×10 4 -150×10 4 The mass fraction of carboxymethyl hydroxypropyl guar gum in the polymerization system is 0.5-5%, more preferably 1-4%, and most preferably 2-3%.

[0016] (2) Adding an initiator to the composite reaction solution to carry out a polymerization reaction at a temperature of -5 to 40°C. When the temperature of the polymerization reaction system rises by no more than 1°C within 30 minutes, the polymerization reaction is considered to be completed, and a polymer colloid is obtained. The polymerization reaction temperature is preferably 10 to 20°C.

[0017] (3) After the polymer colloid is taken out, it is cut, crushed, dried and sieved to obtain a composite copolymer powder. The molecular weight of the powder is 4-12 million.

[0018] The water-soluble solvent is a mixed solvent composed of polyethylene glycol 200, polypropylene glycol 400, and N-methylpyrrolidone, and the mass ratio of polyethylene glycol 200: polypropylene glycol 400: N-methylpyrrolidone is (30-84): (15-60): (1-10). Among them, polyethylene glycol 200 and polypropylene glycol 400 provide a certain viscosity for the suspension system and activate the main suspension agent to achieve suspension stability. N-methylpyrrolidone is a small molecule nitrogen-containing compound, which further reduces the static adsorption amount of polyacrylamide in the reservoir through competitive adsorption. Conventional oil-based suspension drag reducers contain oil in the external phase, so the dispersion speed of the encapsulated polyacrylamide powder in water is slower, and the hydration of the polyacrylamide powder needs to be promoted by the action of penetrants or co-solvent surfactants. The water-soluble solvent of the present invention itself can be quickly miscible with water, so that the composite copolymer powder can be quickly dispersed and dissolved in water.

[0019] The main agent of the suspension is bacterial nanocellulose (BNC), with a diameter of 30-50nm, a crystallinity of 70-90%, and an amount of 0.05-1.0% of the composite copolymer powder, preferably 0.1-0.7%, and optimally 0.3-0.5%. Bacterial nanocellulose is dispersed in a water-soluble solvent and self-assembles to form a three-dimensional network structure through hydrogen bonds. At the same time, there is a hydrogen bond between bacterial nanocellulose and the composite copolymer powder. The use of bacterial nanocellulose as the main agent of the suspension makes the suspension system have excellent stability. At the same time, bacterial nanocellulose itself has excellent degradability, and there is no residue content after degradation, which improves the cleanliness of the product. The traditional suspension system mainly uses organic modified clay as the main agent of the suspension, which has good stability, but also brings a large amount of solid phase residue, causing formation blockage.

[0020] The suspension activator is ethylene glycol or hexamethylphosphoric acid triamide, and the amount added is 0.2%-3% of the composite copolymer powder, preferably 0.5-2%, and optimally 1-1.5%. The composite copolymer powder can form a hydration film under the action of the suspension activator. The formed hydration film makes it difficult for the composite copolymer powder to settle during the collision process in the suspension system, improves the stability of the suspension system, and realizes the rapid dissolution of the powder in water. Among them, hexamethylphosphoric acid triamide can further reduce the adsorption damage of polyacrylamide in different reservoirs.

[0021] The desorption promoter is a sulfonate surfactant, preferably C10-C12 α-olefin sodium sulfonate, and the amount added is 1-15% of the composite copolymer powder, more preferably 3-10%, and most preferably 5-8%. The surfactant can change the wettability of the coal reservoir surface, replace the methane adsorption state through water molecules, and then realize the desorption of methane adsorbed gas.

[0022] The present invention also provides a method for preparing a self-cleaning active drag reducing agent, the steps of which are as follows: S1, preparing a mixed solvent of polyethylene glycol 200, polypropylene glycol 400, and N-methylpyrrolidone; S2, the mixed solvent is divided into two parts, the desorption promoter is added to one part of the mixed solvent, and after stirring for 15 to 20 minutes, the suspension activator is slowly added, and the suspension activator is stirred for 30 minutes to fully mix the suspension activator with the solution, and then the composite copolymer powder is added at a uniform speed while stirring, and the stirring is continued for 1.5 to 2 hours after the addition is completed to obtain a pre-hydrated activated drag reducing agent solution; S3, adding the suspension main agent to another mixed solvent, stirring evenly, to obtain a suspension main agent concentrate; S4, adding the concentrated suspension main agent solution to the drag reducing agent solution of step S2, stirring for 1 hour, and obtaining a self-cleaning active drag reducing agent.

[0023] Compared with the prior art, the present invention is beneficial in that: (1) The present invention introduces a rigid monomer into the polyacrylamide structure to reduce the static adsorption of the drag reducing agent in different reservoirs through steric hindrance. Polyvinyl alcohol and carboxymethyl hydroxypropyl guar gum contain a large number of hydroxyl groups, which can form intermolecular hydrogen bonds with the amide group of polyacrylamide, thereby improving the product's viscosity and sand-carrying performance. A small amount of reinforcing agent is added during the preparation of the composite copolymer to further strengthen the network structure of polyacrylamide and carboxymethyl hydroxypropyl guar gum, and a high content of urea is introduced during the synthesis process. Urea contains NH bonds that compete with polyacrylamide for adsorption on the reservoir, thereby greatly reducing the amount of polymer adsorption, forming a low-adsorption and strong sand-carrying composite copolymer powder.

[0024] (2) The present invention provides a functional self-cleaning fracturing fluid resistance reducing agent that has low adsorption, low residue, self-cleaning, and promotes methane desorption for high-concentration solutions in different reservoirs. It can also be used as a thickener. On the basis of variable viscosity and sand carrying capacity, it further enhances the characteristics of low polymer adsorption and low residue. It also has the function of promoting the dissociation of adsorbed gas into free gas and clearing clean formations, ultimately effectively improving the recovery rate and stable production capacity of oil and gas. Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. DETAILED DESCRIPTION

[0025] The preferred embodiments of the present invention are described below. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0026] In all the examples, unless otherwise specified, the percentage content of each reagent is by mass percentage.

[0027] The experimental evaluation methods used in Examples 1-16 and Comparative Example 1 are as follows: (1) Viscosity average molecular weight test: Use Ubbelohde viscometer (0.55 mm tube diameter) to test and calculate according to GB / T 12005.10-92.

[0028] (2) Static adsorption rate test: Standard curve establishment: Fracturing fluid was prepared according to the formula of 0.2% powder + 0.2% 10% ammonium persulfate aqueous solution, and the fracturing fluid was placed in a 90°C environment to break the gel until the viscosity of the broken gel liquid was less than 5 mPa·s, and a powder broken gel liquid with a concentration of 0.2% was obtained. Here, "0.2% 10% ammonium persulfate aqueous solution" means that ammonium persulfate is first prepared into an aqueous solution with a mass fraction of 10%, and then a 0.2% aqueous solution is added to prepare the fracturing fluid. 2.5mL, 3.0mL, 4.0mL, 4.5mL, 5.0mL of 0.2% powder degelling solution were respectively transferred into a 100mL volumetric flask, fixed to volume with dosing water, and filtered with a 0.45-micron microporous filter membrane, and the 190-240nm UV spectrum of the 5 diluted concentration degelling solutions was measured, and the maximum absorption wavelength λ and the red-shifted and blue-shifted wavelengths of λ by 2-8nm were used for linear fitting of the concentration-absorbance standard curve, and the wavelength closest to 1 at the determination coefficient R2>0.99 was taken as λ. In practical applications, dosing water generally refers to water used on site, which can be lake water, river water, etc. The dosing water used in all embodiments of the present application is deionized water.

[0029] Polymer concentration test of gel-breaking solution before adsorption: Take 4mL of the above 0.2% powder gel-breaking solution in a 100mL volumetric flask, make up to volume with preparation water, and filter through a 0.45-micron microporous filter membrane to obtain the test solution before adsorption. Take the preparation water as a reference, measure the ultraviolet spectrum of the test solution before adsorption at 190nm-240nm, and take the absorbance at wavelength λ1 where the maximum absorption peak is red-shifted (right-shifted) by 6nm as A1.

[0030] Preparation of polymer solution after adsorption: take 10mL of the above-mentioned degelling liquid into a centrifuge tube, add 1g of core powder with a mesh size ≥100 mesh, stir and mix evenly, place it on a 40℃ shaker for adsorption and shaking adsorption for 3h, centrifuge the adsorbed sample in a centrifuge at a speed of 4000r / min for 20min, take 4mL of the middle layer clear liquid into a 100mL volumetric flask, make up to volume with liquid water, and filter it with a 0.45-micron microporous filter membrane.

[0031] Preparation of polymer blank solution after adsorption: take 10mL of preparation water into a centrifuge tube, add 1g of coal powder with a mesh size ≥100 mesh, stir and mix evenly, place it on a 40℃ shaker for adsorption and shaking for 3h, centrifuge the adsorbed sample in a centrifuge at a speed of 4000r / min for 20min, take 2mL of the middle layer clear liquid into a 100mL volumetric flask, make up to volume with preparation water, and filter with a 0.45-micron microporous filter membrane.

[0032] Test of polymer concentration in degelling liquid after adsorption: Taking blank sample after adsorption as reference, measure the UV spectrum of polymer after adsorption at 190nm-240nm, take the absorbance at wavelength λ1 as A2, and calculate the static adsorption amount according to formula (1).

[0033] (1) Where: X—static adsorption rate, %; A2—absorbance of the test liquid at λ1nm after adsorption; A1—Absorbance of the test liquid at λ1nm before adsorption.

[0034] (3) Residue content test Test the 0.2% powder residue content. The test method is carried out and calculated according to method 7.10.3 in SYT 7627-2021 Technical Requirements for Water-Based Fracturing Fluids.

[0035] (4) 85,000 brine viscosity test The water quality composition is 85,000 total mineralization, calcium ions 10,000 mg / L, magnesium ions 1,000 mg / L, and the rest are sodium ions and chloride ions.

[0036] Viscosity test method: under 85,000 saline conditions, add 0.2% powder at a speed of 700r / min, stir at a constant speed for 3 minutes, stop stirring, and use a six-speed rotational viscometer to test the apparent viscosity value at 100r / min.

[0037] Example 1 to Example 16 are examples of the preparation method of composite polymer powder.

[0038] Example 1 Polyvinyl alcohol (molecular weight 60000, alcoholysis degree 80%) and carboxymethyl hydroxypropyl guar gum (molecular weight 120×10 4 ) are dissolved in deionized water at 50°C according to the mass fraction of 2.5% and 2.0% respectively to obtain the initial composite low molecular weight polymer aqueous solution, and then the acrylamide monomer, sodium acrylate, and benzene ring sulfonic acid group-containing rigid monomer are added in a molar ratio of 1:0.2:0.05, and the total mass fraction of the three monomers is 28%. Stir until dissolved, and adjust the pH value of the system to 8 with sodium hydroxide solution. Then add 10% urea and 200mg / L N, N-methylenebisacrylamide in sequence, and dissolve fully to obtain a composite reaction solution. The composite reaction solution is placed in a 15°C constant temperature water bath. When the temperature reaches 15±1°C, a redox initiation system composed of ammonium cerium nitrate and sodium bisulfite is added. The mass ratio of the two is 1:1, and the amount of ammonium cerium nitrate added is 100mg / L of the polymerization system. The polymerization reaction is carried out, and the polymerization reaction is considered to be basically completed when the temperature of the reaction system does not rise by more than 1°C within 30 minutes. One hour after the completion of the polymerization reaction, the colloid was taken out and cut into 3-5 mm particles. The colloid was spread out on a 500-mesh sieve and placed in an oven at a constant temperature of 95°C for 1-3 hours. The colloid was taken out and ground and sieved by a grinder to obtain a low-adsorption and salt-resistant composite polymer powder with a mesh size of ≥120.

[0039] The molecular structure of the rigid monomer containing benzene ring sulfonic acid group is as follows:

[0040] Among them, the R3 group is -SO3Na.

[0041] The viscosity average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 1 is 10.5 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 6.0%, the residue content of 0.2% powder is 20 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 45 mPa·s.

[0042] Embodiment 2: The polyvinyl alcohol (molecular weight 60,000, alcoholysis degree 80%) in Example 1 with an addition amount of 2.5% was changed to polyvinyl alcohol (molecular weight 10,000, alcoholysis degree 80%) with an addition amount of 6%.

[0043] The viscosity average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 2 is 8.53 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 4.5%, the residue content of 0.2% powder is 25 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 32 mPa·s.

[0044] Embodiment 3: The polyvinyl alcohol (molecular weight 60,000, alcoholysis degree 80%) in Example 1 with an addition amount of 2.5% was changed to polyvinyl alcohol (molecular weight 150,000, alcoholysis degree 80%) with an addition amount of 0.5%.

[0045] The viscosity average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 3 is 9.36 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 7.5%, the residue content of 0.2% powder is 32 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 30 mPa·s.

[0046] Embodiment 4: The carboxymethyl hydroxypropyl guar gum (molecular weight 120×10 4 ), the addition amount was 2.0% by mass and changed to carboxymethyl hydroxypropyl guar gum (molecular weight 50×10 4 ), add 5.0%.

[0047] The viscosity average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 4 is 8.2 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 8.0%, the residue content of 0.2% powder is 65 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 36 mPa·s.

[0048] Embodiment 5: The carboxymethyl hydroxypropyl guar gum (molecular weight 120×10 4 ), the addition amount was 2.0% by mass and changed to carboxymethyl hydroxypropyl guar gum (molecular weight 200×10 4 ), add 0.5%.

[0049] The viscosity average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 5 is 11.2 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 5%, the residue content of 0.2% powder is 15 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 33 mPa·s.

[0050] Embodiment 6: The molar ratio of acrylamide monomer, sodium acrylate and benzene ring sulfonic acid group-containing rigid monomer in Example 1 was changed from 1:0.2:0.05 to 1:0.05:0.01.

[0051] The viscosity-average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 6 is 10.85 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 8.9%, the residue content of 0.2% powder is 42 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 27 mPa·s.

[0052] Embodiment 7: The molar ratio of acrylamide monomer, sodium acrylate, and benzene ring sulfonic acid group-containing rigid monomer in Example 1 was changed from 1:0.2:0.05 to 1:0.4:0.1: The viscosity average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 7 is 7.28 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 4.2%, the residue content of 0.2% powder is 85 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 51 mPa·s.

[0053] Embodiment 8: The molar ratio of acrylamide monomer, sodium acrylate and benzene ring sulfonic acid group-containing rigid monomer in Example 1 was changed from 1:0.2:0.05 to 1:0.18:0.06.

[0054] The viscosity average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 8 is 1152, the static adsorption rate of 0.2% powder No. 8 coal rock is 6.2%, the residue content of 0.2% powder is 18 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 54 mPa·s.

[0055] Embodiment 9: The total mass fraction of the three monomers, acrylamide monomer, sodium acrylate, and benzene ring sulfonic acid group-containing rigid monomer, in Example 1 was changed from 28% to 15%.

[0056] The viscosity-average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 9 is 12.03 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 7.0%, the residue content of 0.2% powder is 38 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 42 mPa·s.

[0057] Embodiment 10: The total mass fraction of the three monomers, acrylamide monomer, sodium acrylate, and benzene ring sulfonic acid group-containing rigid monomer, in Example 1 was changed from 28% to 40%.

[0058] The viscosity average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 10 is 6.12 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 4.2%, the residue content of 0.2% powder is 15 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 24 mPa·s.

[0059] Embodiment 11: The amount of N,N-dimethylbisacrylamide added in Example 1 was changed from 200 mg / L to 20 mg / L.

[0060] The viscosity-average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 11 is 9.51 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 5.6%, the residue content of 0.2% powder is 10 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 33 mPa·s.

[0061] Embodiment 12: The amount of N,N-dimethylbisacrylamide added in Example 1 was changed from 200 mg / L to 1000 mg / L.

[0062] The viscosity-average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 12 is 11.25 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 7.5%, the residue content of 0.2% powder is 158 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 18 mPa·s.

[0063] Embodiment 13: The 10% urea in Example 1 was changed to 1% urea.

[0064] The viscosity-average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 13 is 12.15 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 12.5%, the residue content of 0.2% powder is 15 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 42 mPa·s.

[0065] Embodiment 14: The 10% urea in Example 1 was changed to 20% urea.

[0066] The viscosity-average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 14 is 9.38 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 4.0%, the residue content of 0.2% powder is 12 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 30 mPa·s.

[0067] Embodiment 15: The initiation temperature of 15°C in Example 1 was changed to -5°C.

[0068] The amount of ammonium cerium nitrate added in Example 1 was changed from 100 mg / L to 200 mg / L. The viscosity average molecular weight of the low-adsorption salt-resistant composite polymer powder obtained in Example 15 was 9.1 million, the static adsorption rate of 0.2% powder No. 8 coal rock was 5.3%, the residue content of 0.2% powder was 16 mg / L, and the viscosity value of 0.2% powder 85,000 brine was 39 mPa·s.

[0069] Embodiment 16: The initiation temperature in Example 1 was changed from 15°C to 30°C, and the amount of ammonium cerium nitrate added in Example 1 was changed from 100 mg / L to 30 mg / L.

[0070] The viscosity-average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Example 16 is 4.52 million, the static adsorption rate of 0.2% powder No. 8 coal rock is 5.5%, the residue content of 0.2% powder is 10 mg / L, and the viscosity value of 0.2% powder 85,000 brine is 18 mPa·s.

[0071] Comparative Example 1: The acrylamide monomer and sodium acrylate were added in a molar ratio of 1:0.2, and the total mass fraction of the two monomers was 28%. Stir until dissolved, and adjust the pH value of the system to 8 with sodium hydroxide solution. Then add 10% urea and 200 mg / L N, N-methylenebisacrylamide (enhancer) in sequence, and dissolve fully to obtain a polymerization system. The liquid was placed in a 15°C constant temperature water bath. When the temperature reached 15±1°C, a redox initiation system consisting of ammonium cerium nitrate and sodium bisulfite was added. The mass ratio of the two was 1:1, and the amount of ammonium cerium nitrate added was 100 mg / L of the polymerization system. The polymerization reaction was carried out, and the polymerization reaction was considered to be basically completed when the temperature of the reaction system did not rise by more than 1°C within 30 minutes. One hour after the completion of the polymerization reaction, the colloid was taken out, the colloid was cut into 3~5 mm particles, the colloid was spread and laid flat on a 500 mesh sieve, placed in an oven at a constant temperature of 95°C and dried for 1~3h, and taken out and ground and sieved by a grinder to obtain a comparative example 1 polymer powder with a mesh number of ≥120.

[0072] The viscosity-average molecular weight of the low-adsorption and salt-resistant composite polymer powder obtained in Comparative Example 1 is 23.2 million, the static adsorption rate of No. 8 coal rock of 0.2% powder is 14.5%, the residue content of 0.2% powder is 46 mg / L, and the viscosity value of 85,000 brine of 0.2% powder is 12 mPa·s.

[0073] Embodiment 17: According to the formula ratio shown in Table 1, polyethylene glycol 200, polypropylene glycol 400, and N-methylpyrrolidone are pumped into the reactor 1 with a stirring rod in accordance with the formula ratio. After the pumping is completed, the mixed solvent is fully stirred for 15 minutes to obtain a mixed solvent. 70% of the mixed solvent is pumped into the reactor 2, and a desorption promoter is added. The emulsification pump connected to the reactor 2 is turned on. After the circulation stirring is turned on for 15 minutes, the suspension activator is slowly injected during the circulation process so that the suspension activator and the solvent containing the desorption promoter are fully mixed. After the suspension activator is injected and circulated for 30 minutes, the composite copolymer powder is uniformly added to the reactor 2, and the circulation stirring and dispersion are carried out for 1.5-2 hours to obtain a pre-hydrated activated drag reducing agent solution. The suspension main agent is added to the mixed solvent containing 30% mass fraction in the reactor 1, and the emulsification pump is turned on. The circulation stirring is carried out for 30 minutes to obtain the suspension main agent concentrate. The suspension main agent concentrate of the reactor 1 is pumped into the reactor 2. After the pumping is completed, the circulation stirring is carried out for 1 hour to obtain a self-cleaning active drag reducing agent.

[0074] Table 1 Example 17 formulation composition

[0075] Embodiment 18: According to the formula ratio shown in Table 2, the method steps are the same as Example 17.

[0076] Table 2 Composition of Example 18

[0077] Embodiment 19: According to the formula ratio shown in Table 3, the method steps are the same as Example 17.

[0078] Table 3 Composition of Example 19

[0079] Embodiment 20: According to the formula ratio shown in Table 4, the method steps are the same as Example 17.

[0080] Table 4 Composition of Example 20

[0081] Embodiment 21: According to the formula ratio shown in Table 5, the method steps are the same as Example 17.

[0082] Table 5 Composition of Example 21

[0083] Embodiment 22: According to the formula ratio shown in Table 6, the method steps are the same as Example 17.

[0084] Table 6 Composition of Example 22

[0085] Embodiment 23: According to the formula ratio shown in Table 7, the method steps are the same as Example 17.

[0086] Table 7 Composition of Example 23

[0087] Embodiment 24: According to the formula ratio shown in Table 8, the method steps are the same as Example 17.

[0088] Table 8 Composition of Example 24

[0089] Embodiment 25: According to the formula ratio shown in Table 9, the method steps are the same as Example 17.

[0090] Table 9 Composition of Example 25

[0091] Embodiment 26: According to the formula ratio shown in Table 10, the method steps are the same as Example 17.

[0092] Table 10 Composition of Example 26

[0093] Embodiment 27: According to the formula ratio shown in Table 11, the method steps are the same as Example 17.

[0094] Table 11 Composition of Example 27

[0095] Comparative Example 2 (conventional oily suspension drag reducing agent): Into a reactor with a stirring rod, No. 10 white oil was pumped in sequence according to the formula ratio. After pumping, organic bentonite was added and stirred for activation for 30 minutes. Then, a mixed emulsifying dispersant formed by Span 80 and fatty alcohol polyoxyethylene ether was pumped in and stirred for 30 minutes. Then, polymer powder was added to the reactor and stirred for 1-2 hours to obtain an oily suspended drag reducer.

[0096] The formula of Comparative Example 2 is shown in Table 12.

[0097] Table 12 Comparative Example 2 Formulation

[0098] The performance evaluation of the drag reducing agents prepared in Examples 17 to 27 and Comparative Example 2 is as follows: (1) Bulk viscosity test The drag reducing agents of Examples 17 to 27 and Comparative Example 2 were kept at a constant temperature of 25°C for 30 min, and the viscosity values ​​were tested at 100 r / min using a six-speed rotary viscometer. The reading for 1 min was obtained, and the viscosity value was the reading × 3.

[0099] The bulk viscosity test results of Example 17-Example 27 and Comparative Example 2 are shown in Table 13: Table 13 Bulk viscosity test of Examples 17-27 and Comparative Example 2

[0100] (2) 85,000 brine viscosity test The test method is the same as above, and the test results are shown in Table 14.

[0101] Table 14 Apparent viscosity test of Examples 17-27 and Comparative Example 2

[0102] (3) Static adsorption rate test: Standard curve establishment: Fracturing fluid was prepared according to the formula of 0.4% drag reducing agent + 0.2% 10% ammonium persulfate aqueous solution, and the fracturing fluid was placed at 90°C to break the gel until the viscosity of the broken gel was less than 5 mPa·s, and 0.4% drag reducing agent broken gel was obtained. 2.5mL, 3.0mL, 4.0mL, 4.5mL, and 5.0mL of broken gel were respectively transferred to a 100mL volumetric flask, and the volume was fixed with liquid water, and filtered with a 0.45-micron microporous filter membrane. The 190-240nm ultraviolet spectra of the 5 diluted concentration broken gels were measured, and the maximum absorption wavelength λ and the λ red shift and blue shift 2-8nm wavelengths were taken for linear fitting of the concentration-absorbance standard curve, and the wavelength closest to 1 at the determination coefficient R2>0.99 was taken as λ1; Polymer concentration test of gel-breaking liquid before adsorption: Take 4mL of the above 0.4% drag reducing agent gel-breaking liquid in a 100mL volumetric flask, make up to volume with preparation water, and filter it through a 0.45-micron microporous filter membrane to obtain the test liquid before adsorption. Take the preparation water as a reference, measure the 190nm-240nm ultraviolet spectrum of the test liquid before adsorption, and take the absorbance at wavelength λ1 where the maximum absorption peak is red-shifted (right-shifted) by 6nm as A1.

[0103] Preparation of polymer solution after adsorption: take 10mL of the above-mentioned degelling liquid into a centrifuge tube, add 1g of core powder with a mesh size ≥100 mesh, stir and mix evenly, place it on a 40℃ shaker for adsorption and shaking for 3h, centrifuge the adsorbed sample in a centrifuge at a speed of 4000r / min for 20min, take 4mL of the middle layer clear liquid into a 100mL volumetric flask, make up to volume with liquid water, and filter it with a 0.45μm microporous filter membrane.

[0104] Preparation of polymer blank solution after adsorption: take 10mL of preparation water into a centrifuge tube, add 1g of coal powder with a mesh size ≥100 mesh, stir and mix evenly, place it on a 40℃ shaker for adsorption and shaking for 3h, centrifuge the adsorbed sample in a centrifuge at a speed of 4000r / min for 20min, take 2mL of the middle layer clear liquid into a 100mL volumetric flask, make up to volume with preparation water, and filter with a 0.45-micron microporous filter membrane.

[0105] Test of polymer concentration in degelling liquid after adsorption: Taking blank sample after adsorption as reference, measure the UV spectrum of the polymer after adsorption at 190nm-240nm, take the absorbance at wavelength λ1 as A2, and calculate the static adsorption amount according to the following formula.

[0106]

[0107] Where: X—static adsorption rate, %; A2—absorbance of the test liquid at λ1nm after adsorption; A1—absorbance of the test liquid at λ1nm before adsorption; The test results are shown in Table 15.

[0108] Table 15 Static adsorption rate test of Examples 17-27 and Comparative Example 2

[0109] (4) Residue content test The residual content of 0.4% drag reducing agent was tested. The test method was carried out and calculated according to the method 7.10.3 in the technical requirements of water-based fracturing fluids in SYT 7627-2021. The test results are shown in Table 16.

[0110] Table 16 Residue content test of Examples 17-27 and Comparative Example 2

[0111] (5) Drag reduction rate test The drag reduction rate of the drag reducing agent was tested in clean water and 85,000 mg / L salt water (calcium ion 10,000 mg / L, magnesium ion 1,000 mg / L, and the rest were sodium ions and chloride ions) according to the provisions of Chapter 7.13.1.1 of SY / T 6376-2008 for determining the drag reduction rate. The drag reduction rate data of 10 minutes was taken as the drag reduction rate value. The test results are shown in Table 17.

[0112] Table 17 Drag reduction test of Examples 17-27 and Comparative Example 2

[0113] (6) Methane desorption test, the test method is as follows: a. Weigh 50g of coal powder with mesh size of 40-60 respectively and dry to constant weight; b. Put the dried coal sample into the coal sample tank and degas the coal sample in the tank; c. After degassing, high-purity methane gas is filled into the coal sample tank, and the pressure reading of the coal sample tank is adjusted to reach the target value by adjusting the gas inlet and outlet valves. When the pressure reading remains stable within 2 hours, it can be considered that the methane in the tank has reached the adsorption equilibrium state.

[0114] d. Inject 10 mL of the prepared 0.4% resistance reducing agent degelling liquid into the coal sample tank and start the stirring device for 30 minutes.

[0115] e. After the coal sample tank reaches adsorption equilibrium again, connect the gas outlet to the gas collection bag, open the gas outlet valve, and close the gas outlet valve until the pressure indication of the coal sample tank is 0. Open the valve between the methane metering device and the gas outlet of the coal sample tank, and start the timing device at the same time to record the cumulative desorption amount of the coal sample at each time during the subsequent 120-minute desorption process, in mL / g.

[0116] The test results are shown in Table 18.

[0117] Table 18 Methane desorption test of Examples 17-27 and Comparative Example 2

[0118] In summary, the drag reducing agent prepared by the present invention has the functions of low adsorption, low residue, self-cleaning, thickening, etc., and has the function of promoting methane desorption, can be used as a thickening agent, and can be applied to hydraulic fracturing to effectively improve the recovery rate and stable production capacity of oil and gas.

[0119] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment as above, it is not intended to limit the present invention. Any technician familiar with the profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A self-cleaning active drag reducing agent, characterized in that: The components include the following mass percentages: Composite copolymer powder 30-50%, desorption promoter 1-15%, suspension main agent 0.02-0.4%, suspension activator 0.15-0.6%, and the rest is water-soluble solvent, totaling 100%; The preparation method of the composite copolymer is as follows: (1) dissolving polyvinyl alcohol and carboxymethyl hydroxypropyl guar gum in water to form an initial composite low molecular weight polymer aqueous solution, and then adding acrylamide, sodium acrylate, a benzene ring-containing rigid monomer, a reinforcing agent and urea to the aqueous solution to obtain a composite reaction solution; (2) adding an initiator to the composite reaction solution to carry out a polymerization reaction at a temperature of -5 to 40° C. to obtain a polymer colloid; (3) taking out the polymer colloid, cutting, crushing, drying and sieving to obtain a composite copolymer powder; The desorption promoting agent is a sulfonate surfactant; The main suspension agent is bacterial nanocellulose, with a diameter of 30 to 50 nm and a crystallinity of 70 to 90%; The suspension activator is ethylene glycol or hexamethylphosphoric triamide; The water-soluble solvent is a mixed solvent consisting of polyethylene glycol 200, polypropylene glycol 400 and N-methylpyrrolidone.

2. The self-cleaning active drag reducing agent according to claim 1, characterized in that: The molar ratio of acrylamide, sodium acrylate and benzene ring-containing rigid monomer is 1: (0.05-0.4): (0.01-0.1).

3. The self-cleaning active drag reducing agent according to claim 2, characterized in that: The benzene ring-containing rigid monomer is selected from any one of the following six molecular structural formulas: Wherein, the R3 group is -COONa or -SO3Na.

4. The self-cleaning active drag reducing agent according to claim 1, characterized in that: In the composite reaction solution, the mass fraction of polyvinyl alcohol is 0.5-6%, the mass fraction of carboxymethyl hydroxypropyl guar gum is 0.5-5%, the total mass fraction of acrylamide, sodium acrylate and benzene ring-containing rigid monomer is 15-40%, and the mass fraction of urea is 1-20%; the concentration of the enhancer is 20-1000 mg / L.

5. The self-cleaning active drag reducing agent according to claim 4, characterized in that: The enhancer is N,N-methylenebisacrylamide.

6. The self-cleaning active drag reducing agent according to claim 1, characterized in that: The initiator is a redox initiation system composed of ammonium cerium nitrate and sodium bisulfite.

7. The self-cleaning active drag reducing agent according to claim 1, characterized in that: In step (2), the polymerization reaction temperature is 10 to 20°C.

8. The self-cleaning active drag reducing agent according to claim 1, characterized in that: In step (2), the polymerization reaction is considered to be complete when the temperature of the polymerization reaction system does not rise by more than 1° C. within 30 minutes.

9. A method for preparing the self-cleaning active drag reducing agent according to any one of claims 1 to 8, characterized in that: Here are the steps: S1, preparing a mixed solvent of polyethylene glycol 200, polypropylene glycol 400, and N-methylpyrrolidone; S2, the mixed solvent is divided into two parts, the desorption promoter is added to one part of the mixed solvent, and after stirring for 15 to 20 minutes, the suspension activator is slowly added, and the suspension activator is stirred for 30 minutes to fully mix the suspension activator with the solution, and then the composite copolymer powder is added at a uniform speed while stirring, and the stirring is continued for 1.5 to 2 hours after the addition is completed to obtain a pre-hydrated activated drag reducing agent solution; S3, adding the suspension main agent to another mixed solvent, stirring evenly, to obtain a suspension main agent concentrate; S4, adding the concentrated suspension main agent solution to the drag reducing agent solution of step S2, stirring for 1 hour, and obtaining a self-cleaning active drag reducing agent.

Citation Information

Patent Citations

  • Reusable hydraulic fracture resistance reducing agent as well as preparation method and application thereof

    CN103540309A

  • Low-friction drag composite nano-proppant and preparation method thereof

    CN108517205A

  • High-activity drag reducer, self-imbibition energy-increasing extraction type slickwater fracturing fluid system suitable for shale oil reservoir, and preparation method and application thereof

    CN112694885A

  • Temperature-resistant and salt-resistant instant polyacrylamide as well as preparation method and application thereof

    CN115947891A

  • Preparation method of supramolecular self-crosslinking salt-resistant oil-phase-free clean fracturing fluid

    CN118599513A

Cited By

  • Preparation method of aqueous liquid microcapsule gel breaker for fracturing fluid

    CN120519143A

  • Resolution-promoting permeation enhancer and preparation method thereof

    CN121628606A

  • A resolution-promoting permeation enhancer and a method for preparing the same

    CN121628606B